Kelangsungan dan Perlawanan Politik Identitas Dalam Bingkai Keadaban Demokrasi - QODIR, ZULY; LATIEF, SYAHBUDDIN (Universitas Muhammadiyah Yogyakarta, 2011)
This paper is about the sustainability of photographing pelawanan identity politics carried out by civilsociety in the construction of a civilized democracy. This paper shows that the people in his own wayto fight against state policies that are considered political guarantees of political freedoms has occurreddespite the 1998 reform. This paper is based on three case study villages in the Java communityresistance, the imposition of Islamic sharia movement in the NAD and the Liberal Islam movement.The writing in this article uses the perspective of identity politics approach to democracy andcivilization which presupposes the existence of freedom and public participation. The data, carried outby the method of interviews, documentation and discussion focused